Libranos del mal : la corrupción y el desafío para la fe y la iglesia cristiana en América Latina - Laver, Roberto (Regnum studies in mission., 2018)
Very few have made such a substantial contribution to reflection on the factors that contribute to corruption in Latin America as Roberto Laver does in this work. Writing not only from theory but from a contextualized understanding of this problem that directly affects the quality of life of millions of people in Latin America, Laver develops a coherent and relevant proposal for the church today, urging us to open our eyes and respond to the height of our call as the people of God, to strengthen the civic capital of our countries and build fairer societies for the new generations.